The Influence of Service Quality and Interest Rates on the Decision to Take Micro Credit at Bank BRI Medan Branch Hm. Yamin - Setiawan, Reza; Apriani, Wulan; Tasya, Khalisa Aulia; Hasyim, Hasyim (Formosa Journal of Applied Sciences, 2024)
This research aims to determine the influence of interest rate collection behavior and the quality of micro business credit services at Bank BRI, HM Medan branch. yes. This research uses explanatory research, where descriptive statistical methods are used to assess whether there is a relationship between the influence of services provided and interest rates on people's business credit customers. The research results showed that respondents' answers regarding service quality were considered good. The interest rate determination is in line with customer expectations and the results of the credit decision category show that respondents did not experience difficulty in determining the BRI HM Bank branch. Yamin Medan as the bank that submitted the KUR microcredit application.